Management of Waqf Land at Jami Islahuddin Mosque Districts Manggala Makassar City - Putra, Trisno Wardy; Nur Adilah, Azizah; Ruqayyah Yunus, Ayu (UMBanjarmasin, 2021)
The pattern of waqf property management in Indonesia still tends to be in the management traditional pattern. Waqf in Indonesia still has narrowed of its meaning and purpose, the mosques and prayer rooms that were built have not been able to act as a center for driving community activities, and are only used as places of worship. In the city of Makassar, Jami Islahuddin Mosque is one of the Mosque that has been built on waqf land. Therefore, it is deemed necessary to conduct a study of how the management of waqf assets at the Jami Islahuddin mosque. This study uses a qualitative method with field research to describe the existing facts related to the management of waqf land at the Jami Islahuddin Mosque. The data collection technique used is through literature review, observation, interviews and documentation. The results of the study are: The management of the Jami Islahuddin Mosque Waqf Land has been carried out productively. This can be seen from the mosque which is not only used as a place of worship but is also used as an Al-Qur'an Education Center (TPA), Baitul Maal Wa Tamwil (BMT), and the Mosque Business Entity (BUM) Jami Islahuddin Mosque.